2013
DOI: 10.1016/j.devcel.2012.12.013
|View full text |Cite
|
Sign up to set email alerts
|

A bHLH Complex Controls Embryonic Vascular Tissue Establishment and Indeterminate Growth in Arabidopsis

Abstract: Plants have a remarkable potential for sustained (indeterminate) postembryonic growth. Following their specification in the early embryo, tissue-specific precursor cells first establish tissues and later maintain them postembryonically. The mechanisms underlying these processes are largely unknown. Here we define local control of oriented, periclinal cell division as the mechanism underlying both the establishment and maintenance of vascular tissue. We identify an auxin-regulated basic helix-loop-helix (bHLH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
361
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 275 publications
(391 citation statements)
references
References 41 publications
14
361
0
1
Order By: Relevance
“…Nonetheless, we have demonstrated the role of several MP target genes in hypophysis specification (17) and vascular tissue establishment (18,19) through transcriptome profiling of mp seedlings, as well as seedlings in which ARF activity was inhibited by an inducible version of the dominant mutant ARF inhibitor BODENLOS/IAA12 (BDL) (20,21). The BDL transcriptional repressor is normally degraded in response to auxin, resulting in ARF-dependent gene expression (22), but as the bdl mutation prevents degradation (21), this…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Nonetheless, we have demonstrated the role of several MP target genes in hypophysis specification (17) and vascular tissue establishment (18,19) through transcriptome profiling of mp seedlings, as well as seedlings in which ARF activity was inhibited by an inducible version of the dominant mutant ARF inhibitor BODENLOS/IAA12 (BDL) (20,21). The BDL transcriptional repressor is normally degraded in response to auxin, resulting in ARF-dependent gene expression (22), but as the bdl mutation prevents degradation (21), this…”
mentioning
confidence: 86%
“…We thus locally inhibited MP activity in the putative first vascular and ground tissue cells via GAL4-UAS-based (23) expression of a mutant bdl protein to identify embryonic MP target genes. MP controls the stereotypic division of the first vascular cells and hypophyseal cell in the globular-stage embryo (15,18). We crossed UAS::bdl plants with Q0990 plants (Q0990>>bdl) and observed that globular-stage embryos showed vascular and hypophysis division defects after 3 d (Fig.…”
Section: Mp Controls Asymmetric Division In the First Embryonic Groundmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant analyses in Arabidopsis have identified various genes involved in the formation of vascular tissues (1,3,(5)(6)(7)(8)(9). In addition to upstream regulators required for overall vascular morphogenesis, these screens have also identified factors that are specifically involved in xylem or phloem development.…”
mentioning
confidence: 99%
“…Amongst other targets, MP promotes the expression of a basic helix-loop-helix transcription factor, TARGET OF MONOPTEROS 5 (TMO5) (Schlereth et al, 2010). Together with its homologs, TMO5 forms heterodimers with the LONESOME HIGHWAY (LHW) group of helix-loop-helix transcription factors to determine the frequency and orientation of cell divisions within the vascular cylinder (De Rybel et al, 2013;Katayama et al, 2016).…”
Section: Introductionmentioning
confidence: 99%